2014
DOI: 10.1016/j.neuro.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent impacts of low-level lead exposure and prenatal stress on impulsive choice behavior and associated biochemical and neurochemical manifestations

Abstract: A prior study demonstrated increased overall response rates on a Fixed Interval (FI) schedule of reward in female offspring that had been subjected to maternal lead (Pb) exposure, prenatal stress (PS) and offspring stress challenge relative to control, prenatal stress alone, lead alone and lead + prenatal stress alone (Virgolini et al., 2008). Response rates on FI schedules have been shown to directly relate to measures of self-control (impulsivity) in children and in infants (Darcheville et al., 1992; 1993). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 74 publications
2
37
0
Order By: Relevance
“…41 In animal models, sex-specific differences in the effects of Pb exposure have also been observed in spatial learning and memory, motor behavior, dopamine metabolism, and brain gene expression. 8,42,43 Some of the sex-biased response to Pb toxicity can be attributed to sex hormones, or to the differential expression of sex and/or autosomal genes. 44 A mechanism through which exposure to heavy metals such as Pb might contribute to altering gene expression is by changing the 5hmC and 5mC profiles in the genome.…”
Section: Groupmentioning
confidence: 99%
“…41 In animal models, sex-specific differences in the effects of Pb exposure have also been observed in spatial learning and memory, motor behavior, dopamine metabolism, and brain gene expression. 8,42,43 Some of the sex-biased response to Pb toxicity can be attributed to sex hormones, or to the differential expression of sex and/or autosomal genes. 44 A mechanism through which exposure to heavy metals such as Pb might contribute to altering gene expression is by changing the 5hmC and 5mC profiles in the genome.…”
Section: Groupmentioning
confidence: 99%
“…Weston et al showed that when exposed to a more modest dose of Pb during development, male rats are more susceptible to Pb plus stress resulting in changes in neurochemicals and protein production (e.g. BDNF) [46]. Together these studies reviewed here indicate that exposure responses can vary by Pb dose, stress, and sex.…”
Section: Periconceptional Exposures To Lead (Pb)mentioning
confidence: 72%
“…Prevention of lead toxicity mainly involved in the screening of blood lead level in children. Medical intervention is also recommended if lead content is very high in the blood mainly to control blood poisoning [35][36][37][38]. Many preventive measures have been suggested to control lead exposure.…”
Section: Prevention and Control Of Lead-induced Toxicitymentioning
confidence: 99%